Lysine-specific demethylase-1 regulates fibroblast activation in pulmonary fibrosis via TGF-β1/Smad3 pathway. (February 2020) - Pan, Xiaohua; Li, Jiahong; Tu, Xing; Wu, Chengfei; Liu, He; Luo, Yang; Dong, Xiaoliang; Li, Xiu; Pan, Li-Long; Sun, Jia
Graphical abstract: Abstract: Pulmonary fibrosis is a progressive and fatal fibrotic lung disease with mysterious pathogenesis and limited effective therapies. The aberrantly activated lung myofibroblasts with resultant excessive accumulation of extracellular matrix is a central event in the progression of pulmonary fibrosis. Lysine-specific demethylase 1 (LSD1) has been suggested to epigenetically regulate cell differentiation, migration and invasion in tumor microenvironment. However, its function in pulmonary fibrosis remains unclear. The present study aimed to investigate the potential effect and underlying mechanisms of LSD1 in pulmonary fibrosis. Here, we found that LSD1 expression was elevated in lung tissues of mice with bleomycin-induced pulmonary fibrosis and lung fibroblasts treated with transforming growth factor-β1 (TGF-β1). In vivo knockdown of LSD1 by lentiviral shRNA transfection attenuated pulmonary fibrosis in mice, as evidenced by improved lung morphology, decreased lung coefficient and collagen secretion, and down-regulated α-SMA, collagen type I alpha and fibronectin expression in lungs. Additionally, in vitro knockdown of LSD1 inhibited the differentiation of fibroblasts to myofibroblasts, and decreased myofibroblast migration. By further mechanistic analysis, we demonstrated that knockdown of LSD1 prevented fibroblast--to-myofibroblast differentiation and subsequent pulmonary fibrosis by suppressing TGF-β1/Smad3 signaling pathway through modulation of a balance between histone H3 lysine 9 methylation and histone H3 lysine 4 methylation. Together, our data indicate that LSD1 activation contributes to pulmonary myofibroblast differentiation and fibrosis by targeting TGF-β1/Smad3 signaling, and suggest LSD1 as a therapeutic target for the treatment of pulmonary fibrosis.